2020
DOI: 10.3390/ijerph17093140
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Peer Interaction Strengths and Difficulties in Children with Developmental Language Disorder? A Systematic Review

Abstract: The current review gathers together research investigating peer interaction skills in children with Developmental Language Disorder (DLD) to give an overview of the strengths and challenges experienced by these children when interacting with other children. A systematic review was conducted to summarise the literature on peer interaction strengths and difficulties in children with DLD. No restrictions on time-period were made and the selection criteria accounted for many of the diagnostic labels previously use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 65 publications
(157 reference statements)
2
27
0
1
Order By: Relevance
“…This finding suggests that the DLD and RD groups present different profiles in terms of their socio-emotional skills, and not only regarding the nature and severity of their language difficulties, which are more severe in children with DLD ( Laws et al, 2012 ; Mok et al, 2014 ; Lloyd-Esenkaya et al, 2020 ). However, we cannot establish whether there is a direct relationship between language skills and peer difficulties ( Van den Bedem et al, 2018b ).…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…This finding suggests that the DLD and RD groups present different profiles in terms of their socio-emotional skills, and not only regarding the nature and severity of their language difficulties, which are more severe in children with DLD ( Laws et al, 2012 ; Mok et al, 2014 ; Lloyd-Esenkaya et al, 2020 ). However, we cannot establish whether there is a direct relationship between language skills and peer difficulties ( Van den Bedem et al, 2018b ).…”
Section: Discussionmentioning
confidence: 89%
“…The current study aims to analyze bullying experiences and related variables in primary school children with DLD and RD compared to their age-matched peers using teacher reports, peer reports, and self-reports on victimization. Previous research has demonstrated that students with DLD and RD have a higher prevalence of peer problems, poorer acceptance of their classmates, lower quality and quantity of friendships, and larger vulnerability to peer rejection ( Laws et al, 2012 ; Mok et al, 2014 ; Lloyd-Esenkaya et al, 2020 ). However, the accumulating evidence indicates the necessity to distinguish between the perspectives of different reporters and consider the students’ characteristics ( Sidera et al, 2020 ; Gough Kenyon et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations